Evaluation of cartilage and bone metabolism in collegiate athletes belonging to various sports clubs by analyzing type II collagen degradation and synthesis, and type I collagen degradation - Nagaoka, I.; Tsuruta, A.; Yoshimura, M. (Juntendo Medical Journal, 2018)
In this study, to evaluate cartilage and bone metabolism in athletes, the levels of type II collagen degradation marker CTX-II and synthesis marker CPII, and type I collagen degradation marker NTx were measured using urine samples of collegiate athletes belonging to various sports clubs (soccer, tennis, triathlon, squash, swimming, volleyball, kendo, judo, gymnastics, basketball, handball, baseball, long-distance, throwing-event, jumping, sprint and futsal) and compared with those of non-athlete controls (5.11 subjects in each group). NTx levels were significantly increased in soccer, volleyball, basketball and handball players compared with non-athletes. Similarly, CTX-II levels were significantly increased in soccer, volleyball and handball players compared with non-athletes. In contrast, CPII levels were significantly increased in squash players and long-distance runners compared with non-athletes. Moreover, CTX-II/CPII ratios were increased in soccer, volleyball, basketball and handball players compared with non-athlete control, suggesting that type II collagen degradation is relatively increased compared with type II collagen synthesis in these players. Together these observations indicate that cartilage and bone metabolism (type II and type I collagen degradation) is enhanced in players of ball games associated with jumping action, such as soccer, volleyball, basketball and handball.